Investigation of electrical effects on quartz using laser - Zhang, Zhe (2015)
There are many studies on the optical effects due stress and strain in non-linear material. Material quartz is commonly used for our watches oscillator due to its piezoelectric effects. Investigations need to carry on to observe different phenomena, which is the electric effect due to a high power optical excitation. In this project, a femtosecond laser is used to analyze the frequency response of quartz tuning fork. The changing in frequency response has been observed in quartz tuning fork, under a high power optical excitation (femtosecond laser) at room temperature. In addition, the wide ranges of power rating of femtosecond laser (from zero to full power output) were also observed, which exhibited higher response under higher power laser excitation.